Airway Anatomy and Surgical Management in Obstructive Sleep Apnea - Yun Jin Kang; Song Tar Toh; Shintaro Chiba; Clement Cheng-Hui Lin; Chan-Soon Park (Clinical and Experimental Otorhinolaryngology, 2026)
Obstructive sleep apnea (OSA) is a sleep-related breathing disorder characterized by recurrent collapse of a structurally vulnerable upper airway during sleep. Airway caliber and stability are influenced by multiple anatomical structures, including the nasal cavity, soft palate, lateral pharyngeal walls, tongue base, hyoid complex, and craniofacial skeleton. Detailed knowledge of these structures is therefore essential for rational surgical planning. This narrative review summarizes key anatomical features relevant to upper pharyngeal surgery, including nasal obstruction and the internal nasal valve, palatal musculature and parapharyngeal fat, and the lateral palatal space as a target for reconstructive palatal and lateral wall procedures. It also outlines lower pharyngeal strategies, such as genioglossus advancement, hyoid myotomy–suspension, and tongue base reduction, which address retroglossal collapse and unfavorable skeletal–soft tissue relationships. Maxillomandibular advancement and hypoglossal nerve stimulation are discussed as anatomy-driven multilevel and neuromodulatory options, respectively. Across these modalities, an anatomically grounded, phenotype-based approach is central to optimizing patient selection, reducing complications, and improving long-term surgical outcomes in OSA.